Superelectrophilic activation of 5-hydroxymethylfurfural and 2,5-diformylfuran: organic synthesis based on biomass-derived products - Ryabukhin, Dmitry S.; Zakusilo, Dmitry N.; Kompanets, Mikhail O.; A.Tarakanov, Anton; Boyarskaya, Irina A.; Artamonova, Tatiana O.; Khohodorkovskiy, Mikhail A.; Opeida, Iosyp O.; Vasilyev, Aleksander V. (Beilstein Journal of Organic Chemistry, 2016)
The reaction of 5-hydroxymethylfurfural (5-HMF) with arenes in superacidic trifluoromethanesulfonic acid (triflic acid, TfOH) as the solvent at room temperature for 1–24 h gives rise to 5-arylmethylfurfurals (yields of 17–91%) and 2-arylmethyl-5-(diarylmethyl)furans (yields of 10–37%). The formation of these two types of reaction products depends on the nucleophilicity of the arene. The same reactions under the action of acidic zeolites H-USY in high pressure tubes at 130 °C for 1 h result in the formation of only 5-arylmethylfurfurals (yields of 45–79%). 2,5-Diformylfuran (2,5-DFF) in the reaction with arenes under the action of AlBr3 at room temperature for 1 h leads to 5-(diarylmethyl)furfurals (yields of 51–90%). The reactive protonated species of 5-HMF and 2,5-DFF were characterized by NMR spectroscopy in TfOH and studied by DFT calculations. These reactions show possibilities of organic synthesis based on biomass-derived 5-HMF and 2,5-DFF.
Keywords: 2,5-diformylfuran; Friedel–Crafts reaction; 5-hydroxymethylfurfural; superacids; zeolites